Anti-periodic traveling wave solutions to a class of higher-order Kadomtsev-Petviashvili-Burgers equations. (1994) - Aizicovici, Sergiu; Gao, Yun; Wen, Shih-Liang
Abstract : We discuss the existence, uniqueness, and continuous dependence on data, of anti-periodic traveling wave solutions to higher order two-dimensional equations of Korteweg-deVries type.